Optimization of an inset-fed calculations for rectangular microstrip antenna - Sulwan Dase; Irawati Razak (Computer Science and Information Technologies, 2023)
This paper offers an alternative solution to produce a formula to calculate the inset-fed (y0) feed distance from the edge of the patch in order to obtain the impedance of a rectangular patch microstrip antenna as close to 50 Ohm as possible. The basic calculation refers to Ramesh's calculation formula to calculate the inset-fed (y0) on a rectangular patch microstrip antenna. From this research it is hoped that a number of correction factors will be obtained which will be multiplied by the Ramesh formula in order to obtain an inset-fed calculation which results in a lower return loss (S11) and voltage standing wave ratio (VSWR). From several calculation attempts, the approximate value for the correction factor is s=0.83477. This s correction factor is then multiplied by Ramesh's calculation formula. In this experiment, a microstrip antenna was simulated using an FR4 epoxy printed circuit board (PCB) with a relative permittivity, εr= 4.4, with a thickness of h=1.6 mm. The specified antenna nominal input impedance is 50 Ohms. The transmission line used is a microstrip line with a characteristic impedance of 50 Ohm. The test method used is to compare the results of simulation calculations using the Ramesh formula with the results of simulation calculations using the Ramesh formula multiplied by the correction factor. Tests are carried out using varying working frequencies. From the experimental results it can be seen that the average Return Loss (S11) and VSWR of the antenna are lower when using the Ramesh formula with a correction factor compared to the original Ramesh formula.